Straightforward Approach to Ferrocenyl Amino Acids and Peptides by Allylic Alkylation. Issue 20 (3rd June 2013) - Gorges, Jan; Ullrich, Angelika; Kazmaier, Uli
Abstract: Ferrocenylallyl carbonates have been found to be suitable substrates for palladium‐catalyzed allylic alkylation reactions. Amino acid ester and peptide enolates were employed as nucleophiles for the regio‐ and stereoselective introduction of the redox‐active ferrocenyl unit into peptide chains. Abstract : Peptides containing a ferrocenyl side‐chain can easily be obtained in a highly regio‐ as well as stereoselective fashion by palladium‐catalyzed allylic alkylation using ferrocenylallyl carbonates.